An Augmented Reality System for Presenting Architecture Models in Outdoor Scenes - Lin, Jhan-Wei; Chang, Chin-Chen (European Journal of Applied Sciences, 2025)
Due to the rapid development of mobile devices, augmented reality (AR) has been utilized increasingly, and thus applications of AR have increased for indoor and outdoor scenes. However, most of them focus on dealing with indoor scenes and the research for outdoor scenes is rare. In this paper, we propose a system to explore an application of AR for presenting 3D architecture models in outdoor scenes. We aim to enhance the realism of a 3D architectural model for an outdoor scene and provide users with a realistic experience. We first capture a color image through a camera and detect a plane on the image. When obtaining the detected plane, we can generate an anchor and attach virtual objects (3D architecture models) to this anchor. After that, we use the environmental high dynamic range mode of ARCore to obtain lighting information. Thus, our system can present a more realistic light and dark contrast and shadows on the virtual objects. Moreover, we propose an occlusion handling technique to obtain the correct relative positions of real objects and virtual objects. We use a depth prediction model to obtain depth information enabling the real objects to occlude the virtual objects. Finally, the processed augmented color image is rendered. The experiments demonstrate that our system can produce favorable results within a reasonable distance.